Legal Pluralism and the Rights to Pachamama - Antúnez Sánchez, Alcides; Díaz Ocampo, Eduardo (DIXI, 2018)
Aim: To show the constitutional recognition that nature has gained in the Ecuadorian nation, which hasallowed it to be subject of rights and duties as a legal novelty in the construction and evolution of the21 st century, as well as its regulatory development within positive law and public policies. Methods: For this, the historical-legal, analysis-synthesis and induction-deduction methods were em-ployed. Findings: From the last decades of the 20th century, legal pluralism has become relevant due to itsimpact on the social scene. While having various orientations and positions, Philosophy of Law andSociology deal with the definition of new theoretical constructs required to address the essence of legalpluralism in the current context, reevaluating it and providing new aspects of analysis. Conclusions: The Ecuadorian State guarantees the conservation and development of the indigenouspeoples’ traditional forms of coexistence and social organization since they constitute an expression ofinterculturality. This has had a positive effect on the constitutional protection of nature and its regulatorydevelopment based on constitutional texts.
Keywords: Abya Yala; good living; rights of nature; legal pluralism